Radiological disaster response self-efficacy of final-year nursing students and interns at Jazan University, Saudi Arabia - Nasser Shubayr; Shaghf Ahmed; Maria Otif; Maysa Hussain; Hams Khalid; Wasan Bashiri; Hamad Dailh; Mashael Alsairaman; Ali Alfaifi (BMC Medical Education)
Abstract Background Nuclear and radiological accidents pose serious public health risks, requiring healthcare professionals to be prepared with specific response skills. Given the essential role of nurses in disaster situations, this study evaluates the self-efficacy of final-year nursing students and interns at Jazan University, Saudi Arabia, in responding to radiological and nuclear incidents. Assessing self-efficacy levels can highlight strengths and gaps in disaster preparedness, guiding improvements in nursing education. Methods This cross-sectional study was conducted between August and November 2024, involving final-year nursing students and interns recruited through convenience sampling. Data were collected using a modified version of the Disaster Response Self-Efficacy Scale (DRSES), adapted to measure competencies specific to radiological emergencies. The instrument assessed self-efficacy across three subscales “Onsite Rescue”, “Psychological Nursing” and “Role Quality and Adaptation”. Data analysis included descriptive statistics, Pearson’s correlation, independent t-tests, one-way ANOVA, and multiple linear regression to identify predictors of self-efficacy subscales. Results A total of 405 participants were included, with a mean age of 22.08 ± 1.24 years. The majority were female (57.04%). The overall DRSES mean score was 2.89 ± 1.00, and participants with prior disaster training scored significantly higher at 3.36 ± 0.92 compared to those without such training, who scored 2.83 ± 0.99 (p = 0.048). Analysis of the subscales revealed that “Role Quality and Adaptation” achieved the highest mean score (3.08 ± 1.18), followed by “Psychological Nursing” (2.90 ± 1.17), while “Onsite Rescue” received the lowest (2.69 ± 0.93). Strong positive correlations were observed among the three competency domains (r = 0.71–0.88, p < 0.001). Participants reported the least confidence in assessing epidemic risks (2.50 ± 1.21) and performing effective decontamination procedures (2.57 ± 1.24). Interns exhibited greater confidence in “Onsite Rescue” tasks compared to final-year students (β = 0.78, p = 0.034). Conclusions Nursing students demonstrated moderate self-efficacy in radiological disaster response, with strengths in professional role adaptation but weaknesses in technical and assessment-related competencies. The findings underscore the need for targeted educational interventions, including simulation-based training and psychological preparedness modules, to enhance nurses’ confidence and readiness for radiological emergencies.